An eye-tracking study of interpersonal threat sensitivity and adverse childhood experiences in borderline personality disorder - Seitz, Katja I.; Leitenstorfer, Johanna; Krauch, Marlene; Spieß, Karen; Boll, Sabrina; Ueltzhöffer, Kai; Neukel, Corinne; Kleindienst, Nikolaus; Herpertz, Sabine; Bertsch, Katja (Borderline Personality Disorder and Emotion Dysregulation, 2021)
Previous eye-tracking studies provide preliminary evidence for a hypersensitivity to negative, potentially threatening interpersonal cues in borderline personality disorder (BPD). From an etiological point of view, such interpersonal threat hypersensitivity might be explained by a biological vulnerability along with a history of early life adversities. The objective of the current study was to investigate interpersonal threat hypersensitivity and its association with adverse childhood experiences (ACE) in patients with BPD employing eye-tracking technology.